The cinematic works - Ahtila, Eija-Liisa (Helsinki : Crystal Eye, 2005)
- Me/we ##- Okay ##- Gray ##- Me/we (English) ##- Okay (English) ##- Gray (English) ##- Jos 6 olis 9 ##- If 6 was 9 ##- Tänään ##- Today ##- Lohdustusseremonia ##- Consolation service ##- Rakkaus on aarre ##- Love is a treasure.
Finnish language with English subtitles
film
Keywords: Ahtila, Eija-Liisa